The role and regulation of angiogenesis during key stages of ovarian follicle development - Nwachukwu, Chinwe Uchechi (2019)
Over the past five decades, there has been increasing concern over the decline in fertility of ruminants; a multifactorial problem with severe impacts on farmers’ productivity and profitability. Central to reproduction is the adequate and timely function of the ovary. Adequate vascularity underpins many aspects of ovarian function and can be regulated by a range of interacting factors. Firstly, this thesis investigated the role of maternal gestational protein restriction in regulating the development of blood vessels and germ cells in the sheep fetal ovary. This study modelled the potential effects of inadequate nutrition that dairy cows experience during early lactation at a time when they also become pregnant. Importantly, the number of oocytes is established by birth and any inadequacy could lead to premature ovarian failure. The growth of the preovulatory follicle and its transition to the corpus luteum requires intense angiogenesis, which is critical to the tissue remodelling associated with luteinisation. This enables progesterone production to increase sufficiently to support a pregnancy. Insulin-like growth factor 1 (IGF1) and IGF2 are known to regulate multiple ovarian process and are key links between reproduction and metabolic status of the animal. Hypoxia regulates angiogenic factors via activation of hypoxia-inducible factor 1A (HIF1A) to establish a new vasculature in pathological situations, whilst the role of HIF1A in the intense endothelial cells (EC) proliferation that occurs during luteal development is poorly understood. Consequently, this thesis examined the regulation of angiogenesis during key stages of ovarian follicle development via the following studies: investigation of the effect of (1) the insulin-like growth factor system and (2) low oxygen concentration on EC network formation and progesterone production in a bovine luteinising follicular angiogenesis culture system. In the first study, ewes were fed either a control (CP; n=7) or low protein diet (LP; n=8; 17.0 versus 8.7g crude protein) from conception to day 65 of gestation. After slaughter, fetal ovaries were subjected to histological (Haematoxylin and Eosin staining, Periodic-Acid Schiff staining) and immunohistochemical (OCT4, VASA, DAZL, Ki67, Caspase 3, CD31 expression) analysis. Mean fetal weight (p>0.05) was unaffected by diet, whilst protein restriction reduced fetal ovary weight (p<0.05) at day 65 of gestation. The percentage area of cortex and germ cell density were unaffected by maternal diet (p>0.05), whilst low protein reduced the estimated total weight of germ cells (p<0.05), by approximately 30%. There was an abundance of OCT4, DAZL and VASA-positive germ cells in the fetal ovarian cortex, with OCT4 being the most abundantly expressed. There was no effect of maternal diet on the density, estimated weight, total volume, and total number of OCT4, DAZL, and VASA-positive cells (p>0.05). Maternal protein restriction did not affect germ cell proliferation or apoptosis or alter the ovarian vasculature (p>0.05). In the second study, bovine luteinising follicular angiogenesis cultures were treated 1) with LR3-IGF1 or IGF2 (10 or 100 ng/ml) in the absence and presence of FGF2+VEGFA (1 ng/ml), or 2) with IGF1 receptor inhibitor (picropodophyllin (PPP); 1 µM) in presence or absence of LR3-IGF1, IGF2, or combined LR3-IGF1+IGF2 (10 ng/ml), or 3) with luteinising hormone (5 or 50 ng/ml) in the presence or absence of LR3-IGF1 (10 ng/ml) for 5 days. EC networks were quantified by von Willebrand factor immunohistochemistry. Progesterone production was analysed by ELISA and cell proliferation was determined by MTT assay. IGF1R expression was assessed in bovine ovarian tissue sections and cultured cells. LR3-IGF1 and IGF2 had limited effects on EC growth parameters, whilst PPP (p<0.001) markedly reduced EC growth parameters (by 60-70%). Cell proliferation was slightly increased (by 3-5%) by LR3-IGF1 (p<0.001) and IGF2 (p<0.05) treatment. LR3-IGF1 and IGF2 had small and variable effects on progesterone production, whilst PPP reduced progesterone concentration (p<0.001) with or without LR3-IGF1 or IGF2 alone or in combination. LH (50 ng/ml) increased IGF1 concentrations (p<0.001). IGF1R was expressed in antral follicles, corpora lutea and cultured cells. In the third study, bovine luteinising follicular angiogenesis cultures were incubated under control (20%) or low (3%) oxygen conditions. Cells were further cultured in the absence or presence of angiogenic-stimulation (FGF2+VEGFA; 1 ng/ml), with or without HIF1A inhibitor (echinomycin; 1 µM), and with or without PKA inhibitor (H89; 10 µM). EC growth parameters were quantified. Progesterone, lactate, and VEGFA concentrations were analysed in culture media by ELISA and cell proliferation determined by MTT assay. Western blotting was performed for expression analysis of steroidogenic proteins (STAR, CYP11A1 and HSD3B1), HIF1A and HIF1A responsive proteins (PGK1, GLUT1, and BNIP3), and a marker of mural cells (ACTA2). Low oxygen reduced EC growth parameters (p<0.001; by 35%) and progesterone production (p<0.05; by 35-55%). HIF1A inhibition via echinomycin treatment also reduced EC growth parameters (p<0.001; by 30%) and progesterone production (p<0.01; by 35-40%), in both 20% and 3% oxygen. Total cell proliferation, lactate production, ACTA2 expression and VEGFA concentrations were unaffected by oxygen conditions (p>0.05) but were decreased by echinomycin (at least p<0.05), in both 20% and 3% oxygen. This was particularly marked for VEGFA, where echinomycin reduced expression by 6-fold. The steroidogenic proteins, HIF1A and HIF1A-responsive proteins and ACTA2 were expressed by cultured follicular cells. Low oxygen reduced STAR expression (32 kDa; p<0.05) but did not affect CYP11A1 or HSD3B1 expression (p>0.05). Echinomycin reduced HSD3B1 expression in 3% oxygen only (p<0.05), but did not affect STAR or CYP11A1 expression (p>0.05). HIF1A-responsive BNIP3 expression was reduced (p<0.01) and PGK1 tended to be reduced (p=0.06) by echinomycin treatment, in both 20% and 3% oxygen. In contrast, GLUT1 was unaffected by echinomycin (p>0.05). The reduction of the total EC network area by low oxygen was partially reversed by the addition of H89 (p<0.05). H89 reduced the number of branch points and degree of branching (p<0.05) but had no effect on the other EC network parameters. In addition, progesterone production was unaffected by H89 (p>0.05). In summary, this thesis has shown the following: 1) maternal protein restriction had limited effect on fetal ovarian development in sheep; 2) Endogenous IGF1 and/or IGF2 production plays an important role in stimulating bovine follicular angiogenesis; 3) Low oxygen reduced progesterone production as expected, but contrary to our hypothesis low oxygen did not stimulate EC growth. Furthermore, many of the responses to HIF1A inhibition were observed at both 20% and 3% oxygen, suggesting that HIF1A may play a critical role in angiogenesis and steroidogenesis that is independent of oxygen environment. The negative effects of low oxygen on EC networks are possibly mediated in part by PKA signalling. In conclusion, this thesis further highlights the complex regulation of bovine follicular angiogenesis.